Evaluation of the total sulfur amino acid requirement of finishing pigs - Loughmiller, J.A.; Smith, J.W.II; Bergstrom, J.R.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Sixty four gilts (initially 120 lb) were used to evaluate the effects of increasing total sulfur amino acid (TSAA):lysine ratios on growth performance and carcass characteristics. Diets included two levels of lysine (.55% and .70% total lysine) and three TSAA:lysine ratios (60, 65, and 70% of lysine) arranged in a 2 x 3 factorial. A tendency for a lysine x TSAA interaction was observed for ADG and ADFI. Increasing TSAA:lysine ratio decreased ADG and ADFI in pigs fed .55% lysine; however, ADG and ADFI were increased in pigs fed .70% lysine and 65% TSAA:lysine. Pigs fed .70% lysine had improved ADG, F/G and 10th rib fat depth compared to those fed .55% lysine. However, no effects were observed with increasing TSAA: lysine ratios. These results suggest that the TSAA requirement of finishing pigs is not greater than 60% of total lysine.
Keywords: Swine; Finishing pigs; Methionine; Amino acids